Reduction of Destructive Multipath Signal Effects in Radio Propagation Using Adaptive Equalization Technique - N., Nwanoruo M.; A., Okoye J.; B., Mbachu C. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Radio signals transmitted through propagation channels are subject to fading, dispersion, and distortion, often resulting in communication errors such as inter-symbol interference. These impairments, largely influenced by atmospheric conditions and physical obstructions, alter signal behavior during transmission. This study evaluates the effectiveness of adaptive equalization techniques in mitigating the adverse effects of destructive multipath signals in wireless and radio communication systems. A Rayleigh fading channel model was employed, and an adaptive algorithm was implemented to approximate the desired filter by minimizing the least mean square error (MSE) of the output signal. System performance was assessed using source recovery error as a cost function to correct delays and recover the transmitted information. Two equalization strategies—decision-directed and dispersion minimization algorithms—were developed to reduce multipath-induced errors. Results showed that adaptive equalization significantly reduced signal ripple. The decision-directed equalizer exhibited faster convergence but higher steady-state error, achieving an optimal MSE value of 10⁻² and outperforming the dispersion minimization approach. These findings confirm the effectiveness of adaptive equalization in enhancing communication reliability under fading channel conditions.